Métodos geofísicos aplicados na prospecção geológica de terrenos - Cardoso, João Luís (2017)
Concise presentation of geophysic methods applied on the characterization of the geological structures are presented. His objective is to reveal near the archaeologists some methods applied in other sciences, preceding posterior work, about geophysical archaeological prospection.